A Continuously Tunable Solid‐Like Convective Thermal Metadevice on the Reciprocal Line. Issue 42 (9th September 2020) - Li, Jiaxin; Li, Ying; Cao, Pei‐Chao; Yang, Tianzhi; Zhu, Xue‐Feng; Wang, Wuyi; Qiu, Cheng‐Wei
Abstract: The emerging thermal metamaterials and metadevices demonstrate significant potential to transform thermal conduction. However, the thermal conductivities of existing devices are all restricted at fixed values if the configuration or constituent materials are static. Thermal convection provides an additional tool to boost and flexibly modify the heat transfer in moving matter, but it is essentially distinct from thermal conduction since the Onsager reciprocity is generally broken in the former but preserved in the latter. Therefore, it is difficult to use convective components for sophisticated control of conductive heat. Here, it is shown that a convective system can be made undistinguishable from a conductive one in principle, by discovering and operating on the reciprocal line of mechanically rotating systems. The realized thermal metadevice can thus mimic a solid‐like material whose thermal conductivity dynamically covers a wide range. It offers great possibilities of real‐time smooth control over heat transfer for broad applications. Abstract : A solid‐like convective thermal metadevice is proposed. This device can disguise any target as a solid material with a continuously tunable thermal conductivity in a wide range. This is achieved by restoring the reciprocity of a convective system on the reciprocal line, based on its effective thermal conductivity.